Stereophotogrammetric analysis of pushing kinematics of wheelchair rugby players on an inertial ergometer - Petrone, N.; Benazzato, M.; Bettella, F.; Sacerdoti, P.; Marcolin, G.; Masiero, S. (Proceedings, 2018)
The aim of the work was the kinematic analysis of pushing technique of four wheelchair rugby players using a stereophotogrammetric motion capture system. The four players presented an increasing level of ability expressed by their wheelchair rugby classification point. An original contribution of the work is the fact that exercises were recorded on an inertial drum ergometer with players using their own game wheelchair. The ergometer inertia was tuned to reproduce the linear inertia of each player: subjects performed sprint tests without additional resistance and Wingate tests. The Initial Contact and Hand Release values at the wheel were recorded for each test in the early stages and at the end. The shoulder flexion/extension angle and the elbow flexion angle were plotted against each other to highlight a tendency to a synchronous joint kinematics with increasing classification points.